Conjugated HCl-doped polyaniline for photocatalytic oxidative coupling of amines under visible light. Issue 3 (18th January 2019) - Kong, Peng; Liu, Pei; Ge, Zhenyu; Tan, Hao; Pei, Linjuan; Wang, Jie; Zhu, Pengqi; Gu, Xianmo; Zheng, Zhanfeng; Li, Zhong
Abstract : Conjugated HCl-doped polyaniline acted as an efficient visible light-responsive nonmetal photocatalyst for imine green synthesis. Abstract : HCl-Doped polyaniline (PANI-ES) and PANIs of different oxidation states were prepared by a typical oxidative polymerization and subsequent redox reaction, respectively. The photocatalytic performance of PANIs towards selective benzylamine oxidation reactions under visible light was investigated. PANI-ES containing a polaron structure exhibited the highest light-induced activity (54.9%). The results show that the formation of the surface complex between PANI-ES and adsorbed amine should be responsible for the enhanced visible light activity. The newly formed polaron band in PANI-ES has a greater number of delocalized electrons, which can facilitate electron transfer and thus improve the photoactivity. These results indicate that conjugated conducting polymers can be efficient visible light-responsive nonmetal photocatalysts for green synthesis.